1998
DOI: 10.1017/s0305000997003358
|View full text |Cite
|
Sign up to set email alerts
|

Why are some verbs learned before other verbs? Effects of input frequency and structure on children's early verb use

Abstract: This study investigated the extent to which the nature of verb input accounts for the order in which children acquire verbs. We assessed the nature of verb input using a combined sample of the speech of 57 mothers addressing their Stage I children. We assessed the order of verb acquisition using as our database a combined sample of those children's speech 10 weeks later and using as our measure of order of acquisition the frequency of verb occurrence. The first set of analyses established the vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
215
2
12

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 350 publications
(242 citation statements)
references
References 28 publications
13
215
2
12
Order By: Relevance
“…Hayes & Clark, 1970;Newman, 2008 ;, artificial language learning (Gillette, Gleitman, Gleitman & Lederer, 1999 ;Kachergis, Yu & Shiffrin, 2012;Plaut & Kello, 1999 ;Recchia, Johns & Jones, 2008 ;Yu & Smith, 2007), and rapid and diverse vocabulary acquisition (e.g. Hoff & Naigles, 2002;Hurtado, Marchman & Fernald, 2008 ;Huttenlocher, Haight, Bryk, Seltzer & Lyons, 1991 ;Naigles & Hoff-Ginsberg, 1998 ;Rowe, 2008). On the other hand, consistency (i.e.…”
Section: University Of Warwickmentioning
confidence: 99%
“…Hayes & Clark, 1970;Newman, 2008 ;, artificial language learning (Gillette, Gleitman, Gleitman & Lederer, 1999 ;Kachergis, Yu & Shiffrin, 2012;Plaut & Kello, 1999 ;Recchia, Johns & Jones, 2008 ;Yu & Smith, 2007), and rapid and diverse vocabulary acquisition (e.g. Hoff & Naigles, 2002;Hurtado, Marchman & Fernald, 2008 ;Huttenlocher, Haight, Bryk, Seltzer & Lyons, 1991 ;Naigles & Hoff-Ginsberg, 1998 ;Rowe, 2008). On the other hand, consistency (i.e.…”
Section: University Of Warwickmentioning
confidence: 99%
“…Rumelhart and McClelland 1986), take statistical properties of the input to be the primary determinant of development, and some acquisition studies have shown that the relative frequency of particular pieces of morphology (e.g. Hseieh et al (1999)) and of particular lexical items such as verbs (Naigles and Hoff-Ginsberg 1998) correlate with their order of acquisition in the child's language. It has also been proposed that the acquisition of particular syntactic constructions, for example wh questions, is affected by the relative frequency of specific wh + verb combinations in the input (Rowland et al 2003).…”
Section: Frequency Effects In the Acquisition Of The Malagasy Voicesmentioning
confidence: 99%
“…The addition of another frame might have helped the toddlers figure out the authors' intended meaning of the verb (i.e. syntactic bootstrapping with multiple frames, which has been shown to facilitate toddlers' production and comprehension of verbs; Gleitman, 1990;Landau & Gleitman, 1985;Naigles, 1996Naigles, , 1998Naigles & Hoff-Ginsberg, 1998). Moreover, it effectively demonstrated to the children that each verb could be produced in more than one way; this variability could have helped overcome the production problems detailed in Section 3.2 above.…”
Section: A Meaning-based Reinterpretation Of the Experimental (Novel mentioning
confidence: 99%